Hilirisasi Penelitian Rekontruksi Sains Ilmiah Berbasis Pengetahuan Masyarakat Mengenai Budaya Ngeteh Sebagai Kearifan Lokal Bangsa Indonesia - Sudarmin; Widiyatmoko, Arif; Setiawan, Beni; Sri Endang Pujiastuti, Rr (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
Indonesia has known tea and ngeteh culture since its ancestors and until now this culture has been preserved. Thus "Ngeteh" is the local wisdom of the Indonesian people. The community also has knowledge about the diversity of tea, the benefits of tea for health, how to make tea, and know the taste and aroma of tea. This research aims to downstream the results of the reconstruction of the original knowledge of the community into a culture of tea in the context of ethnoscience as a vehicle for learning chemistry, as well as for the conservation of tea culture as a form of Indonesian local wisdom. This type of research is research with an ethno-scientific approach which includes data collection activities, verification and reduction, conceptualization and validation, as well as scientific reconstruction and explanation. The results of the reconstruction of scientific knowledge are documented as a learning resource for organic chemistry of natural materials and to equip students with the character of local wisdom. Data analysis was carried out in a descriptive qualitative manner regarding the results of the reconstruction of scientific knowledge based on community knowledge regarding the Ngeteh culture. The results of the study were concluded. The results of the analysis of the discussion data can be concluded (1) the process of reconstruction and explanation of the community's knowledge about tea, tea water, tea making, tea culture and its benefits for health has been produced, (2) informants as research subjects stated that tea and tea have been well known by the people of Indonesia and tea has benefits for the body (3) the method of making tea, ngeteh, and the taste of tea water contains scientific concepts related to chemical concepts regarding the process of extraction, oxidation, enzymatic reactions, and (3) in tea, tea water contains secondary metabolites of alkaloids, flavonoids, tannins and saponins which cause bitterness and cure disease